2018
DOI: 10.1101/334599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compensatory evolution drives multidrug-resistant tuberculosis in Central Asia

Abstract: Bacterial factors favoring the unprecedented multidrug-resistant tuberculosis (MDR-TB) epidemic in the former Soviet Union remain unclear.We utilized whole genome sequencing and Bayesian statistics to analyze the evolutionary history, temporal emergence of resistance and transmission networks of MDR-MTBC strains from Karakalpakstan, Uzbekistan (2001-2006).One MTBC-clone (termed Central Asian outbreak, CAO) with resistance mediating mutations to eight anti-TB drugs existed prior the worldwide introduction of st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 26 publications
(43 reference statements)
0
26
0
Order By: Relevance
“…Cases with resistance beyond the four drugs/drug classes defining extensively drug-resistant TB (XDR-TB, resistance to isoniazid, rifampicin, at least one second-line injectable and a fluoroquinolone) are the result of further acquisition of resistance [1][2][3], primary (transmitted) resistance [4] or a combination thereof [5]. Strains of the Beijing lineage of the Mycobacterium tuberculosis complex have previously been associated with an increased ability to develop multidrug resistance (MDR, resistance to at least isoniazid and rifampicin) and spread [6][7][8]. Examples are the documented outbreaks in Russia [9] and South Africa (Gauteng Province) [10], as well as the widespread transmission of a highly resistant strain in the Eastern Cape (EC) Province of South Africa [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cases with resistance beyond the four drugs/drug classes defining extensively drug-resistant TB (XDR-TB, resistance to isoniazid, rifampicin, at least one second-line injectable and a fluoroquinolone) are the result of further acquisition of resistance [1][2][3], primary (transmitted) resistance [4] or a combination thereof [5]. Strains of the Beijing lineage of the Mycobacterium tuberculosis complex have previously been associated with an increased ability to develop multidrug resistance (MDR, resistance to at least isoniazid and rifampicin) and spread [6][7][8]. Examples are the documented outbreaks in Russia [9] and South Africa (Gauteng Province) [10], as well as the widespread transmission of a highly resistant strain in the Eastern Cape (EC) Province of South Africa [4].…”
Section: Introductionmentioning
confidence: 99%
“…To validate the method within a clinical setting we analyzed data from a study conducted in Uzbekistan between 2003 and 2008 30,46 , which was approved by the Médecins Sans Frontières international ethics review board. This already published study addressed the development of OFX resistance and the development of XDR-TB during MDR-TB treatment 30,46 . At that time the IS6110 DNA fingerprint method was used to check samples for re-and mixed infection 30 .…”
Section: Methodsmentioning
confidence: 99%
“…(9) A recent expansion of drug-resistant isolates in the country is linked to the spread of "successful" Central Asian/Russian sublineage of M. tuberculosis Beijing genotype. (10) At the same time, a number of studies have reported rapid acquisition of drug-resistance in the LAM family including KZN isolates from South Africa and LAM-RUS sublineage widespread in Kazakhstan and its neighboring countries. (8,11) In previous studies, the LAM genetic family was found at a proportion of 11% in a sample of 470 M. tuberculosis isolates from 12 provinces of Kazakhstan (51/470 = 10.85%).…”
mentioning
confidence: 99%